A Conversational Analysis of a Lesson in the School - Idress Mohammed, Suha (Al-Mudarris: Journal Of Education, 2021)
The interaction between the teachers and the students determines the success of the teaching learning process. Teaching dose not only involve the transmission or reception of information as well as it is a chance for conversation and discussion. The aim of this study is that to analyze how teacher-student interaction is expressed conversationally, i.e., how it is started and closed. It is also intended to describe the discoursal structure of verbal interaction as reflected in the classroom. The study hypothesises that  the teacher- student discourse structure is complex, and the main speaker is the teacher. As well as the students are not passive listeners. Finally , the study has come up with that the teacher and the student have an effective role in the classroom.